Structural characterization and protective effects of polysaccharides isolated from Berberis dasystachya M. fruits on H2O2-induced oxidative damage in RINm5F pancreatic β-cells - Xiaohang Lu; Lijuan Han; Yongrong Deng (Frontiers in Nutrition)
Our previous research demonstrated the hypoglycemic and antioxidant properties of crude polysaccharides from Berberis dasystachya M. (BDP), but the structural characteristics and underlying mechanisms were unclear. In this study, a homogeneous polysaccharide, BDP-I, was isolated and structurally characterized. BDP-I had a molecular weight of 3.947 kDa and consisted of arabinose, galactose, glucose, and galacturonic acid, mainly linked through →6)-β-D-GalAp-(1→ glycosidic bonds.An oxidative stress model was established by treating RIN-m5F pancreatic islet cells with 250 μmol/L H2O2 for 3 hours. BDP-I intervention at concentrations ranging from 0.0625 to 0.5 mg/mL significantly improved cell viability, reduced reactive oxygen species (ROS) and thiobarbituric acid reactive substances (TBARS), and enhanced superoxide dismutase (SOD) and catalase (CAT) activities in a dose-dependent manner.Untargeted metabolomics revealed that BDP-I regulated 46 potential biomarkers, effectively reversing metabolic disturbances caused by oxidative stress. In addition, BDP-I modulated the expression of genes associated with apoptosis and mitochondrial damage, including iNOS and NF-κB.These findings suggest that BDP-I exerts protective effects against oxidative damage in pancreatic islet cells through multiple mechanisms, highlighting its potential as a targeted antioxidant agent for functional food or therapeutic applications.